Simulação física por retificação da soldagem de dutos com processo GMAW - Magalhães, Víctor Augusto Nascimento (2012)
The increasing demand for expansion of pipelines for the flow of many different types of fluids, requires joining processes with higher productivity. However, research in the welding of pipes to bypass the on purchasing, handling, joint preparation, quantity and size of the tubes. If was possible to weld plates instead of pipes, simulating the positions and other conditions of welding of pipes, the search process would become quite optimized. This is the proposal of Pipeline Welding Simulator by Rectification. Coupled with the ease of welding plates instead of pipes, it is proposed to also use processes with high productivity (compared to the SMAW, which is still used) in an automated way. Thus, the objective of this work is the study of the pipeline welding using GMAW and conventional sources in order to control short-circuit (derivative proceedings). This work presents the root pass welding with the use of short-circuit metal transfer (conventional and derivative). It will be evaluated beyond the necessity of weaving, three different weaving techniques to measure which is most suitable. It was also necessary to make improvements on the stand in general experimental conditions to suit the needs of existing simulation of welding of pipes. Among these improvements, a study was conducted and construction of a system for controlling speed of a DC motor. There was also a structural reinforcement in the handler that promotes the trajectory of the torch (TARTÍLOPE). There were then welds the simulator varying the welding parameters and shielding gas (Ar+25% CO2 and pure CO2) for the root pass using initially the metal transfer GMAW process with short-circuit conventional , and then processes GMAW metal transfer to short-circuit controlled using commercial source RMD (Regulated Metal Deposition) manufacturer Miller, commercial source STT (Surface Tension Transfer) and manufacturer\'s Lincoln commercial source CMT (Cold Metal Transfer) of manufacturer Fronius. The analysis of the weld beads obtained through visual inspection and metallographic analysis (Macrography) based on the criteria of acceptability of API standard 1104, attested to the ability of processes to perform quality welds in the simulation of the union of the pipes. Based on the results of the analyzes, it was possible to set operating ranges for each of the cases studied.